Character Index of Mathematics and Science Student Teachers in Online Learning - Parmin Parmin; Iwan Junaedi; Eling Purwantoyo; Ibnul Mubarak; Mukhammad Toni; Fifit Fitriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Online learning changes learning habits from face to face to distance learning. The purpose of the study is to measure the character index of mathematics and science student teachers in online learning during the COVID-19 pandemic. The study used mixed methods, collecting and analyzing quantitative data through questionnaires targeting Mathematics and Science student teachers, followed by qualitative data through interviews. The questionnaire used a Likert five scale option. The number of research targets was 340 student teachers with 224 women and 116 men. The results obtained are four indicators of mathematics and science student teachers characters in online learning that are less than optimal, consisting of beginning and ending lectures by praying, attendance, and politeness while optimal in the timeliness indicator collecting assignments with an index of 4.40 from a maximum index of 5.00. The study concludes that online learning has an impact on the character index of student teachers.